Analisisi Peningkatan Perkawinan Usia Anak di Kecematan Tempe Kabupaten Wajo Perspektif Maqasid Syar'iah: Analisisi Peningkatan Perkawinan Usia Anak di Kecematan Tempe Kabupaten Wajo Perspektif Maqasid Syar'iah - Tantri, Tantri Indar Pratiwi; Hasan, Hamzah; Hilal, Fatmawati (International Journal of Islamic Studies, 2024)
The main problem in this study is how to analyze the increase in child marriage in Tempe District, Wajo Regency, from the Maqasid Syar'iah Perspective? The main problem is then broken down into several sub-problems or research questions, namely: 1) What are the Causes of the Increase in Child Marriage in Tempe District, Wajo Regency? 2) What are the solutions to reduce the increase in child marriage in Tempe District, Wajo Regency? 3) How is Maqasid Syar'iah Perspective on Increasing Child Marriage in Tempe District, Wajo Regency? his type of research is classified as qualitative with the research approach used is a juridical approach, a syar'i approach, and a sociological approach. The data sources of this research are Furthermore, the data collection methods used are observation, interviews, documentation, and reference tracing. Then, data processing techniques and data analysis were carried out through several stages, namely: data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that 1) The factors that cause an increase in child marriage in Tempe sub-district, Wajo Regency, are: a) educational factors; b) economic factors; c) cultural factors; d) community mindset factors; e) factors of pregnancy out of wedlock. 2) Solutions in suppressing the increase in child marriage in Tempe District are: a). Provide services in the field of administration including registration of marriage, divorce and reconciliation as well as other records related to the duties and roles of KUA; b) Providing Counseling and Socialization of the Marriage Law; c) Providing services in the field of marriage and sakinah families. 3) Maqashid Sharia perspective on child marriage Whether or not child marriage can be seen from one maqashid point of view, such as hifz al-nasl to avoid adultery. 1) However, it is also necessary to look at other maqashid values ​​so that the sharia maqashid analysis does not overlap. 2) The implications of this research are: 3) For the people of Tempe District, Wajo Regency, to always follow and obey all government regulations, especially regarding Law no. 16 of 2019 concerning marriage. The local government should give warnings or sanctions for people who violate the rules of Law no. 16 of 2019 concerning Marriage, especially the age limit. 3) KUA employees in the field of penghulu can optimize the penghulu to socialize and emphasize the importance of getting married according to the age limit that has been determined by law. Both through marriage advice and when invited to religious activities.